The Influence Brand Equity And Store Atmosphere In Consumer Loyalty Through Consumer Satisfaction At Jember Urban Store: English - R. Hedy Ubaidillah; Yuniorita Indah Handayani; Muhaimin Dimyati (Yayasan Pendidikan Belajar Berdikari, 2025)
This Study aims to test the effect of brand equity, store atmosphere on consumer loyalty through consumer satisfaction at the urban store Jember. The data for this study were obtained from distributing questionnaires to the research object with a sampling technique using purposive sampling. This type of research is quantitative. The sample used in this study was consumers of the urban store Jember with a total of 50 respondents. Data analysis used validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, path analysis, determination coefficient test using the SPSS 25 program. The results of this study indicate that brand equity, store atmosphere directly significant to consumer loyalty at the urban store Jember.